Rates of attrition, non-compliance and missingness in randomized controlled trials of child physical activity interventions using accelerometers: A brief methodological review - Howie, Erin; Straker, Leon (2015)
© 2016 Sports Medicine Australia. Objectives: The purpose of this brief review was to describe the missingness, from both attrition and non-compliance, during physical activity randomized controlled trials among children which have used accelerometers to measure physical activity. Design: Systematic review. Methods: Using a previously published search strategy, an updated search of the literature was performed in the MEDLINE database for articles published from 1996 to February 2015 identifying physical activity RCTs in children (ages 2-18) measuring physical activity using accelerometers. Rates of attrition and non-compliance were extracted from identified articles. Twenty-three independent studies provided complete attrition and non-compliance data and were included. Results: The mean attrition rate was 11.5% (SD 10.1%, range 0-30.9%). The mean accelerometer non-compliance rate at baseline was 22.7% (SD 16.4%, range 1.7-67.8%) and 29.6% (SD 19.4%, range 3.3-70.1%) at follow-up. The mean total study missingness was 37.4% (SD 20.2%, range 3.3-75.4%) and ranged from 3.3% to 75.4%. There was large variation in how missingness was accounted for between studies. There were no statistically significant differences in missingness between study characteristics including sample size, participant age, intervention setting, duration of follow-up, whether physical activity was the primary outcome, and weartime compliance criteria. Conclusions: Missingness is common among randomized controlled trials using accelerometry in children and is currently handled inconsistently. Researchers must plan for high levels of missingness in study design and account for missingness in reporting and analyses of trial outcomes.